2021
DOI: 10.3390/nu13124263
|View full text |Cite
|
Sign up to set email alerts
|

Association between Daily Niacin Intake and Glaucoma: National Health and Nutrition Examination Survey

Abstract: Background and Aims: To determine the relationship between dietary intake of niacin and glaucoma using the data from the 2005 to 2008 National Health and Nutrition Examination Survey (NHANES). Methods: Subjects aged 40 years and older who participated in the dietary intake interview and vision health questionnaire of NHANES were included in the study. Glaucoma diagnosis by self-report was utilized. Additionally, glaucoma diagnosis by fundus imaging and International Society Geographical and Epidemiological Oph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Research on the relationship between niacin or molybdenum and MD proves challenging to find. Meanwhile, niacin has been shown to have potentially adverse ocular effects ( [64], [65]) while still offering some promise for glaucoma prevention [66].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the relationship between niacin or molybdenum and MD proves challenging to find. Meanwhile, niacin has been shown to have potentially adverse ocular effects ( [64], [65]) while still offering some promise for glaucoma prevention [66].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 DM was diagnosed according to a reported reference definition [15]. PACG was diagnosed based on the criteria of the International Society for Geographical and Epidemiological Ophthalmology (ISGEO) [16]. Briefly, PACG diagnosis was defined by a primary anatomic narrow-angle (180°or more of iridotrabecular contact assessed by indentation gonioscopy and ultrasound biomicroscopy (SW-3200L, Suoer Electronic Technology Co., Ltd., Tianjin, China)), with glaucomatous optic neuropathy (a vertical cup/disc [C/D] ratio >0.7 and/or C/D asymmetry >0.2 and/or focal notching of the neuroretinal rim), and compatible visual field defects measured using the Octopus 900 perimeter (Haag-Streit Inc., Köniz, Switzerland).…”
Section: Patients' Recruitmentmentioning
confidence: 99%
“…34 Furthermore, a recent report evaluating the publicly available data from the 2005 to 2008 National Health and Nutrition Examination Survey (NHANES), showed that the odds of having glaucoma were lower when the consumption of vitamin B3 was higher. 35 This article attempts to analyze the current knowledge regarding the use of vitamin B3, more specifically NAM and NR, for the prevention and/or treatment of glaucoma. For this review, 49 articles, published between 2000 and 2022, containing the terms "glaucoma" and "nicotinamide" were identified in PubMED.…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, a recent report evaluating the publicly available data from the 2005 to 2008 National Health and Nutrition Examination Survey (NHANES), showed that the odds of having glaucoma were lower when the consumption of vitamin B3 was higher. 35…”
Section: Introductionmentioning
confidence: 99%